Effects of acarbose on cardiovascular and diabetes outcomes in patients with coronary heart disease and impaired glucose tolerance (ACE): a randomised, double-blind, placebo-controlled trial. Issue 11 (November 2017) - Holman, Rury R; Coleman, Ruth L; Chan, Juliana C N; Chiasson, Jean-Louis; Feng, Huimei; Ge, Junbo; Gerstein, Hertzel C; Gray, Richard; Huo, Yong; Lang, Zhihui; McMurray, John J; Rydén, Lars; et al.
Summary: Background: The effect of the α-glucosidase inhibitor acarbose on cardiovascular outcomes in patients with coronary heart disease and impaired glucose tolerance is unknown. We aimed to assess whether acarbose could reduce the frequency of cardiovascular events in Chinese patients with established coronary heart disease and impaired glucose tolerance, and whether the incidence of type 2 diabetes could be reduced. Methods: The Acarbose Cardiovascular Evaluation (ACE ) trial was a randomised, double-blind, placebo-controlled, phase 4 trial, with patients recruited from 176 hospital outpatient clinics in China. Chinese patients with coronary heart disease and impaired glucose tolerance were randomly assigned (1:1), in blocks by site, by a centralised computer system to receive oral acarbose (50 mg three times a day) or matched placebo, which was added to standardised cardiovascular secondary prevention therapy. All study staff and patients were masked to treatment group allocation. The primary outcome was a five-point composite of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, hospital admission for unstable angina, and hospital admission for heart failure, analysed in the intention-to-treat population (all participants randomly assigned to treatment who provided written informed consent). The secondary outcomes were a three-point composite outcome (cardiovascular death, non-fatal myocardial infarction, and non-fatal stroke), death from any cause, cardiovascular death, fatal or non-fatal myocardial infarction, fatal or non-fatal stroke, hospital admission for unstable angina, hospital admission for heart failure, development of diabetes, and development of impaired renal function. The safety population comprised all patients who received at least one dose of study medication. This trial is registered withClinicalTrials.gov, numberNCT00829660, and the International Standard Randomised Controlled Trial Number registry, number ISRCTN91899513. Findings: Between March 20, 2009, and Oct 23, 2015, 6522 patients were randomly assigned and included in the intention-to-treat population, 3272 assigned to acarbose and 3250 to placebo. Patients were followed up for a median of 5·0 years (IQR 3·4–6·0) in both groups. The primary five-point composite outcome occurred in 470 (14%; 3·33 per 100 person-years) of 3272 acarbose group participants and in 479 (15%; 3·41 per 100 person-years) of 3250 placebo group participants (hazard ratio 0·98; 95% CI 0·86–1·11, p=0·73). No significant differences were seen between treatment groups for the secondary three-point composite outcome, death from any cause, cardiovascular death, fatal or non-fatal myocardial infarction, fatal or non-fatal stroke, hospital admission for unstable angina, hospital admission for heart failure, or impaired renal function. Diabetes developed less frequently in the acarbose group (436 [13%] of 3272; 3·17 per 100 person-years) compared with the placebo group (513 [16%] of 3250; 3·84 per 100 person-years; rate ratio 0·82, 95% CI 0·71–0·94, p=0·005). Gastrointestinal disorders were the most common adverse event associated with drug discontinuation or dose changes (215 [7%] of 3263 patients in the acarbose group vs 150 [5%] of 3241 in the placebo group [p=0·0007]; safety population). Numbers of non-cardiovascular deaths (71 [2%] of 3272 vs 56 [2%] of 3250, p=0·19) and cancer deaths (ten [<1%] of 3272 vs 12 [<1%] of 3250, p=0·08) did not differ between groups. Interpretation: In Chinese patients with coronary heart disease and impaired glucose tolerance, acarbose did not reduce the risk of major adverse cardiovascular events, but did reduce the incidence of diabetes. Funding: Bayer AG.